Effect of glycerol feed in methanol induction phase for hepatitis B surface antigen expression in Pichia pastoris strain KM71 - Morvarid, Akhavan Rezaei; Allaudin, Zeenathul Nazariah; Tam, Yew Joon; Hassan, Zuridah; Mohd Lila, Mohd Azmi; Othman, Azizon (Universiti Putra Malaysia Press, 2012)
This study describes expression of HBs Ag in methylotrophic yeast, Pichia Pastoris under alcohol oxidase promoter. A single copy number of HBs Ag gene was transformed into pichia strain of KM 71, a Mutˢ type, by using pA0815 pichia expression vector. The recombinant was cultivated in a shake flask either using methanol or a mixed feed of glycerol -methanol for induction. The HBs Ag gene integrity was justified using direct PCR method. The expressed products in the soluble cell extracts were analyzed by Western blot, SDS page, Bradford assay and ELISA tests. The recombinant HBs Ag was expressed successfully in Pichia pastoris strain KM71 at a high level of HBs Ag protein expression. Thus, an addition of glycerol in the ratio of glycerol per methanol 1/1 (g g-1) consistently produced 2-fold increment in both biomass accumulation and HBs Ag productivity.